(untitled) (Годишен зборник на Филозофски факултет - Скопје, 2022)
This study is an initial analysis of the functioning of the brief form of the Individual Work Performance Questionnaire (IWPQ) translated in Macedonian language. IWPQ measures three dimensions of job performance across wide variety of jobs and by assessing work performance, contextual performance and counterproductive behaviour. The sample was comprised of 404 employees (55.7% women) from 14 occupational backgrounds, with average age M = 38 (SD = 12.1) and average working experience M = 12.6 (SD = 10.4) years. All participants voluntarily answered the online based instrument which included demographic data, IWPQ, OLBI and the UWES, sent at their personal e-mail addresses. Descriptive statistics, item-analysis, confirmatory factor analysis and correlations with two other included constructs were performed in order to explore the psychometric characteristics of the instrument in this particular cultural context. Results confirmed the tridimensional structure of IPWQ with marginal fit indicators, while the Alpha coefficients suggested adequate reliability of the scales (α=0.73-0.86). The construct dimensions exhibit significant associations with other measures expected to be related to work performance. It was concluded that although the IWPQ version translated in Macedonian is adequate to be used as a measure of job performance, further research, particularly adjustment of the content of items might contribute to improvement of its validity.